Melanopsin phototransduction: slowly emerging from the dark. - Hughes, S; Hankins, M; Foster, R; Peirson, S (2012)
Melanopsin expressing retinal ganglion cells represent a third class of ocular photoreceptors and are involved in irradiance detection and non-image-forming responses to light including pupil constriction, circadian entrainment, and regulation of sleep. Over recent years, there has been a rapid increase in our understanding of the anatomical variety of pRGC subtypes, the regions of the brain which they innervate, and the behavioral responses of melanopsin-based light detection. However, by contrast, our understanding of the intracellular signaling cascade initiated following activation of melanopsin has, until recently, remained poorly characterized. This chapter focus on the melanopsin signaling pathway, detailing the cellular mechanisms of phototransduction that occur within pRGCs, highlighting recent advances, but also the gaps in our understanding of this important light detecting system.